Impact-investments: myths and reality ("Journal "U". Economy. Management. Finance.", 2023)
The article examines the concepts of impact investing and social business as innovations based on social values and the desire to make the world a better place. The authors believe that such investments are aimed not only at achieving social and environmental results, but also at generating commercial profit. Examples of successful socially oriented businesses are given, as well as the authors urge the reader to consider investments as a means of achieving socially significant goals. The authors strive to change outdated ideas about business and its impact on society, convincing readers of the importance of the social orientation of business.
Keywords: social investing; impact investing; social effect; Global Impact Investing Network; commercial profit; social business; myths